PERANCANGAN SISTEM INFORMASI AKUNTANSI PENGENDALIAN PERSEDIAAN BBM KAPAL LAUT DENGAN MENERAPKAN METODE EOQ - Kasih Purwantini; Eni Endaryati; Iwan Koerniawan (Universitas Sains dan Teknologi Komputer, 2021)
This study aims to develop a fuel inventory control system so that it can facilitate monitoring the volume of fuel stock from each bunker ship and can be reported at any time, so that the leadership can estimate the addition of fuel orders to PT. Pertamina for each bunker ship that is adjusted to the incoming fuel request order. If there is a sudden fuel order by the customer, the company can still serve the customer well, so that the fuel stock can be controlled and can be monitored properly at any time. The research method used in the information system monitoring the pump fabrication process is Research and Development (R&D) in this study only until the 6th (sixth) stage and produces the final product in the form of a prototype, so it does not reach the product implementation stage. The six steps are Research and information collecting, Planning, Develop preliminary form of product, Preliminary field testing, Main product revision and Main field testing. This application is made using Macromedia Dream Weaver and MySQL database.